2021
DOI: 10.3390/safety7040071
|View full text |Cite
|
Sign up to set email alerts
|

Ergonomics and Human Factors as a Requirement to Implement Safer Collaborative Robotic Workstations: A Literature Review

Abstract: There is a worldwide interest in implementing collaborative robots (Cobots) to reduce work-related Musculoskeletal Disorders (WMSD) risk. While prior work in this field has recognized the importance of considering Ergonomics & Human Factors (E&HF) in the design phase, most works tend to highlight workstations’ improvements due to Human-Robot Collaboration (HRC). Based on a literature review, the current study summarises studies where E&HF was considered a requirement rather than an output. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 42 publications
(206 reference statements)
1
18
0
Order By: Relevance
“…Recent reviews in the field of HFE and cobot implementation have focused on specific interactions which take place in sociotechnical systems: for example, two reviews focused on the applications and features of HRC from a task planning and operations management perspective, that we classified as L‐S interaction (Hashemi‐Petroodi et al, 2020; Tsarouchi et al, 2016). Another review demonstrated that HFE issues are rarely considered as requirement when designing collaborative robotic workstations, suggesting that further work should be undertaken to create a comprehensive framework to allow an assessment of both physical and mental workload during human‐cobot interaction (Cardoso et al, 2021). Several authors reviewed methods to ensure physical safety in industrial HRC applications (Reddy et al, 2019; Robla‐Gomez et al, 2017), without considering aspects related to mental health.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reviews in the field of HFE and cobot implementation have focused on specific interactions which take place in sociotechnical systems: for example, two reviews focused on the applications and features of HRC from a task planning and operations management perspective, that we classified as L‐S interaction (Hashemi‐Petroodi et al, 2020; Tsarouchi et al, 2016). Another review demonstrated that HFE issues are rarely considered as requirement when designing collaborative robotic workstations, suggesting that further work should be undertaken to create a comprehensive framework to allow an assessment of both physical and mental workload during human‐cobot interaction (Cardoso et al, 2021). Several authors reviewed methods to ensure physical safety in industrial HRC applications (Reddy et al, 2019; Robla‐Gomez et al, 2017), without considering aspects related to mental health.…”
Section: Discussionmentioning
confidence: 99%
“…The first phenomenon stems from the reduction of the work time cycle and the consequent requirement for operators to move faster [ 28 ]. The latter can be an effect of anxiety or lack of expertise and confidence in interacting with robots [ 15 ], the execution of time-sharing activities [ 21 ], switching the operator’s role from a co-operant to a supervisor [ 21 , 89 ], repeatability of the operator’s movements [ 10 ], or the lack of inclusion of participants’ preferences for the task shared with a robot [ 31 , 90 ].…”
Section: The Study Aims and Hypothesesmentioning
confidence: 99%
“…For operators, automated robotic systems can help prevent adverse health effects [ 16 ] during work in unsafe environments [ 20 ]. Generally, the surge of interest in collaborative robots stems from the fact that they are seen as technological solutions for improving performance [ 1 , 7 , 21 ]. More than that, however, scholars and practitioners suggest that cobots enhance operators’ well-being [ 1 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although mechanical hazards from controlled set-ups can be accurately predicted, it is much harder to understand interaction failures, maladaptation of decision making, and possible psychosocial effects. Although there is growing attention to these human factors [48], there is still a need to gain a better understanding of these risks from what is known as the second age of safety. Typically, these are not risks that can be controlled with one-for-all solutions, but rather, they require safety management frameworks to enable the monitoring, analysis, and management of these risks.…”
Section: Cobot Safety Is Dynamic and Not Limited To The Consideration...mentioning
confidence: 99%